Jaringan Ulama: Pembaharuan dan Rekonsiliasi dalam Tradisi Intelektual Islam di Dunia Melayu-Indonesia - Oman Fathurahman (Studia Islamika, 2004)
Book Review: Azyumardi Azra, The Origins of Islamic Reformism in Southeast Asia: Networks of Malay-Indonesian and Middle Eastern 'Ulama' in the Seventeenth and Eighteenth Centuries, Australia: Allen & Unwin, 2004, ix + 254 pagesThis book attentpts to enrich and -in a number of important ways- also to revise this nomenclature of "Islamic reformism". Taking modernism as its starting point, this book explains Islamic reformism by tracing the historical path of the important concept of shari'ah in the religious thoughts and practices of Muslim's, and how it became the dominant discourse. This concept was voiced by prominent Indonesian 'ulama' in the 17th and l818 centuries. More importantly, this concept emerged parallel to their intellectual contact with the Haramayn 'ulama'(in Mecca and Medina), which gave rise to the process of Islamic transmission through a complex network of student-teacher relationships. This process, known as the 'ulama' network, is the focus of discussion in this book.DOI: 10.15408/sdi.v11i2.606